the f(x)

Algebra Level 2

If f ( 2 x + 1 ) = 3 x + 2 f(2x+1) = 3x +2 , find f ( 4 x + 3 ) 6 x f(4x+3) - 6x .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Given that

f ( 2 x + 1 ) = 3 x + 2 = 3 2 ( 2 x + 1 ) + 1 2 f ( x ) = 3 2 x + 1 2 f ( 4 x + 3 ) 6 x = 3 2 ( 4 x + 3 ) + 1 2 6 x = 6 x + 9 2 + 1 2 6 x = 5 \begin{aligned} f(2x+1) & = 3x + 2 = \frac 32 (2x+1) + \frac 12 \\ \implies f(x) & = \frac 32 x + \frac 12 \\ \therefore f(4x+3) - 6x & = \frac 32(4x+3) + \frac 12 - 6x \\ & = 6x + \frac 92 + \frac 12 - 6x \\ & = \boxed 5 \end{aligned}

@Chew-Seong Cheong Hello sir .
Are you creating your own website like Brilliant ,i have heard that.
Like community in Brilliant?

Talulah Riley - 3 days, 12 hours ago

Log in to reply

I don't have the skills. I am looking for someone to host it.

Chew-Seong Cheong - 3 days, 12 hours ago
Saya Suka
Jun 9, 2021

4x + 3 = 2(2x + 1) + 1

Answer
= f(4x + 3) – 6x
= f(2(2x + 1) + 1) – 6x
= [ 3(2x + 1) + 2 ] – 6x
= 6x + 3 + 2 – 6x
= 5

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...